2020
DOI: 10.3389/fimmu.2020.600000
|View full text |Cite
|
Sign up to set email alerts
|

CD86 Is a Selective CD28 Ligand Supporting FoxP3+ Regulatory T Cell Homeostasis in the Presence of High Levels of CTLA-4

Abstract: CD80 and CD86 are expressed on antigen presenting cells and are required to engage their shared receptor, CD28, for the costimulation of CD4 T cells. It is unclear why two stimulatory ligands with overlapping roles have evolved. CD80 and CD86 also bind the regulatory molecule CTLA-4. We explored the role of CD80 and CD86 in the homeostasis and proliferation of CD4+FoxP3+ regulatory T cells (Treg), which constitutively express high levels of CTLA-4 yet are critically dependent upon CD28 signals. We observed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…We also observed high CD86 levels in the advanced tumor, which are supported by the presence of high CD86 B cell signatures in advanced stages of other cancers [63]. However, a high degree of CD80 expression, along with CD86 and increased transcript numbers of T-cell counter receptors (CD28 and CTLA4) (data not shown) in tumors also point out the costimulatory roles of CD86/CD80, which are known to induce T cell anergy [64]. The differential expression of these immune markers highlights a unique immunophenotype of the Rb tumors that requires further exploration to understand their roles in tumor growth and its progression of severity.…”
Section: Discussionsupporting
confidence: 71%
“…We also observed high CD86 levels in the advanced tumor, which are supported by the presence of high CD86 B cell signatures in advanced stages of other cancers [63]. However, a high degree of CD80 expression, along with CD86 and increased transcript numbers of T-cell counter receptors (CD28 and CTLA4) (data not shown) in tumors also point out the costimulatory roles of CD86/CD80, which are known to induce T cell anergy [64]. The differential expression of these immune markers highlights a unique immunophenotype of the Rb tumors that requires further exploration to understand their roles in tumor growth and its progression of severity.…”
Section: Discussionsupporting
confidence: 71%
“…As expected, blockade of CD86-CTLA-4 interactions was achieved at lower doses, suggesting that CD80 ligands may be more readily available than CD86 at a sub optimal doses of antibody, which may occur during therapy. A paradox in anti-CTLA4 therapy is that blocking CTLA-4 should lead to excess CD28 co-stimulation, which could lead to increased Treg expansion as has been reported in vivo ( 23 ) and as we have shown in vitro ( 24 ). Whilst CTLA4 suppressive function will be blocked other Treg suppressive mechanisms may still function, potentially affecting outcomes in anti-tumour immunity.…”
Section: Discussionmentioning
confidence: 60%
“…It is interesting that we have observed that antibody blockade experiments show a more inhibited phenotype when CD86 is blocked compared with CD80, even when both ligands are co-expressed. In addition, we have observed that CD86 is a more effective CD28 ligand for stimulating activated T cells and T reg cells in the presence of high levels of CTLA-4, where it has an advantage in sustaining extended cell division and higher levels of CD25, inducible co-stimulator and CD40L 42,47 . Thus, in an activated immune system where CTLA-4 is expressed on all activated T cells, CD86 is likely to be the more important CD28 ligand, capable of sustaining stimulation in the face of CTLA-4 competition.…”
Section: Discussionmentioning
confidence: 96%